Application of Albert Bandura’s Social-Cognitive Theories in Teaching and Learning - Mujahidah, Nelly; Yusdiana, Yusdiana (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article aims to describe and analiyze about Bandura's theory, commonly known as social-cognitive learning theories. This Theories was developed to explain how a person experiences learning in the surrounding environment. Bandura argues that environmental behavior and internal events in learning that affect perception and action are mutually influential relationships. Learning is a triangular interaction that is mutually influential and binding between the environment, personal factors and behavior which includes cognitive processes of learning. The learning components consist of behavior, the consequences of the model and the learner's cognitive processes. Social cognitive theory has two main implications for education. First, modeling is the main source of information for students. This theory identifies situations in which children obtain information from models in the mass media as well as from family and other models. The second is the importance of a sense of efficacy/personal efficacy and self-regulation ability to be a successful learner. Learning outcomes are in the form of visual and verbal codes that may or may not be retrieved. In planning complex skill learning, in addition to learning the components of the skill itself, it is necessary to develop a sense of efficacy and learner self - regulation . In the learning process, learners should be given sufficient opportunity for mental training before physical exercise, and reinforcement and avoid unnecessary punishment. In learning process according to theory social Albert bandura, a teacher must could presenting good models. Its must could have influence which strong to learners so that could give attention for them. Model here no must from teacher, however depends what which will taught. Theory social study suitable for teaching psychomotor and affective domain, because learners direct could notice, remember and copy from model which presented